2017
DOI: 10.1039/c7nr03018e
|View full text |Cite
|
Sign up to set email alerts
|

Modular interior loading and exterior decoration of a virus-like particle

Abstract: Virus-like particles (VLPs) derived from the bacteriophage P22 offer an interesting and malleable platform for encapsulation and multivalent presentation of cargo molecules. The packaging of cargo in P22 VLP is typically achieved through genetically enabled directed in vivo encapsulation. However, this approach does not allow control over the packing density and composition of the encapsulated cargos. Here, we have adopted an in vitro assembly approach to gain control over cargo packaging in P22. The packaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(90 citation statements)
references
References 56 publications
2
88
0
Order By: Relevance
“…Previous work has shown that P22 and phage L behave similarly [33,34,36] and all of the amino acid substitutions found in phage L have even been identified occasionally in P22 stocks as phenotypically silent mutations (Teschke lab, unpublished data). Lastly, as Dec bound to P22 is a widely used system for a variety of nanomaterials applications [10,42,43], identifying key residues that contribute to Dec interactions with P22 is highly useful for practical applications. Therefore, we felt it reasonable to use the established genetics of P22 as a model for the native phage L for our mutagenesis studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that P22 and phage L behave similarly [33,34,36] and all of the amino acid substitutions found in phage L have even been identified occasionally in P22 stocks as phenotypically silent mutations (Teschke lab, unpublished data). Lastly, as Dec bound to P22 is a widely used system for a variety of nanomaterials applications [10,42,43], identifying key residues that contribute to Dec interactions with P22 is highly useful for practical applications. Therefore, we felt it reasonable to use the established genetics of P22 as a model for the native phage L for our mutagenesis studies.…”
Section: Resultsmentioning
confidence: 99%
“…Defining the mechanisms by which different decoration proteins, such as gpD and Dec, bind viral particle surfaces is not only important for understanding the underlying biology, but is also critical for (1) the potential exploitation of phages in nanomedicine [3740], (2) structure-guided design of virus-inspired nanomaterials [10,36,4144], and (3) sheding light on capsid assembly and stabilization processes [29,45]. Here, we investigate how Dec is able to distinguish subtly different capsid binding sites with high specificity.…”
Section: Introductionmentioning
confidence: 99%
“…Preliminary studies indicate that a glutathione S‐transferase‐scaffoldign construct (GST‐scaffold) can indeed be incorporated into PLPs and that the enzyme retains wild‐type catalytic activity to afford an efficient nano‐bioreactor (Chang, McClary and Catalano, unpublished). Of note, a similar approach has recently been reported in the P22 system (Sharma et al, ).…”
Section: Lambda Plps Containing “Cargo”mentioning
confidence: 87%
“…As is well known, virus RNA carrier exhibits high transfection efficiency, but at the cost of strong immunogenicity. Virus‐like nanoparticles have therefore been developed as gene and drug carriers from different plant protein or Hepatitis B core protein …”
Section: Nanomaterials For Cancer Precision Therapymentioning
confidence: 99%